Optimization of the spill quality for the hadron therapy at the Heidelberg Ion-Beam Therapy Centre - Cortés García, Edgar Cristopher; Feldmeier, Eike; Galonska, Michael; Schömers, Christian; Hun, M.; Brons, Stephan; Cee, Rainer; Scheloske, Stefan; Peters, Andreas; Haberer, Thomas (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2022)
The Heidelberg Ion-Beam Therapy Centre???s synchrotron makes use of the well established slow extraction RF KO method near the third-order resonance. The spill quality is essential for therapy, since the reproducibility and fidelity in the parameters of the extracted beam translate in a reduction of irradiation time. The horizontal beam response was studied experimentally and with simulations at extraction conditions in order to deduce regions of interest for an optimal excitation signal spectrum. Two narrow frequency regions were found near the betatron resonance. With these results a new signal was engineered for the emittance blow-up scheme. The new excitation signal improves significantly the spill quality for the extraction configurations; for instance the lower interquartile value of the spill duty factor distribution for the most rigid carbon-ion beam E-kin = 430 MeV/u improves from 82.2% to 94.8%. For the proton beam the improvement is more significant, where the spill duty factor is kept over the 90% level.
Gesehen am 24.11.2022